Pola Komunikasi Humanistik antara Orang Tua dan Anak atas Dampak Negatif Bermain Online Game pada Prestasi di Sekolah Dasar - Kencanawati, Rahayuning Tirta; Fitriyani, Lamria Raya (Calathu: Jurnal Ilmu Komunikasi, 2021)
Nowadays online games are played by various groups, starting with adults to the young especially children in elementary school and Mobile Legends is one online game that is played by children. However, sometimes children playing this online game over time impact their grade and achievement in school. The purpose of this research was to understand humanistic communication patterns between parents and elementary school children regarding the negative impact of playing Mobile Legends on school achievement. All information was gathered through interviews with three families whose child played Mobile Legends in total eight interviewees. The method used was descriptive qualitative and data analysis method from Miles, Huberman & Saldana. The results signified the interpersonal humanistic communication approach in two families were suitable for the five stages that are openness, empathy, supportiveness, positiveness, and equality. Whereas in one other family was not suitable for the five stages of the humanistic approach, but only the four stages and there was no equality. The results indicated the balanced split pattern of two families and the other one family refers to the unbalanced split pattern. Keywords: humanistic communication patterns, communication family, online game